ANALISIS PEMANFAATAN LIMBAH BATU BARA BOTTOM ASH SEBAGAI FILLER TERHADAP DURABILITAS DAN FLEXIBILITAS ASPAL BETON AC – WC - Rosyad, Farlin; Andini, Novi Tri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Roads are the basic and main infrastructure in driving the wheels of the national and regional economy, considering their important and strategic function to encourage the distribution of goods and services as well as population mobility. The availability of roads is an absolute prerequisite for the entry of investment into an area. Roads enable all communities to gain access to education, health and employment services. For this reason, it is necessary to plan a pavement structure that is strong, durable and has high resistance to plastic deformation that occurs. The most widely used road pavement in Indonesia is asphalt concrete or laston (AC/Asphalt Concrete). Laston has a high level of flexibility so that placement directly on layers such as wear (WC - Wearing Course) makes this layer vulnerable to damage due to high temperatures and heavy traffic loads. The types of damage that often occur in laston are grain release and cracking. In an effort to add substitutes for fine materials that can be used as ingredients in asphalt mixtures, coal ash, which is easily obtained, was used in research as an alternative fine material in asphalt mixtures. The oil asphalt used is Pertamina asphalt with a penetration of 60/70. This research was carried out with the aim of finding out the optimum mixture value of coal ash as a substitute for fine material for concrete layers or laston (AC – WC) and to find out how much influence the fineness of coal ash as a substitute for fine material has on AC – WC laston in terms of Durability and Flexibility. The percentage of coal ash content used in this study was 1%, 2%, 3% and 4% for Normal, zone 0, zone 1 and zone 2 as a substitute for fine material in the AC – WC asphalt mixture and normal test specimens without coal ash. This research uses the Marshall test method by reviewing the effect of coal ash on durability and flexibility values. Based on the results of testing marshall parameters in terms of zone variations and percentage of coal ash substitution content, it can be concluded that the flow value in standard marshall coal ash percentages of 1%, 2% and 3% meets the 2018 Bina Marga Specifications revision 2 between 2 - 4 mm. Meanwhile, the coal ash percentage of 4% does not meet the 2018 Bina Marga Specifications revision 2, between 2 - 4 mm. Because the greater the percentage of coal ash, the greater the flow value obtained. In terms of Marshall Stability, it can be concluded that the residual Marshall Stability value for a normal AC - WC asphalt mixture is 90.67%, this value meets the 2018 Bina Marga Specifications Revision 2 with Specification Standards >90%.Keywords: Layered laston mixture (AC – WC), Durability, Flexibility, Coal Waste (Bottom Ash), Marshall